Neuro-Pedagogy of the visual arts in reading comprehension - Pompa-Montes de Oca, Luis Alberto; Muñoz-Cedeño, Alfonso Wenceslao; Alcívar-Ferrín, Juan Diego; Montesdeoca-Chávez, Martha Elizabeth; Cedeño-Molina, Jorge Isacio (International research journal of management, IT and social sciences, 2025)
The research, titled "Neuropedagogy of the Visual Arts in Reading Comprehension," sought to investigate and gather answers to the problems posed and seek to resolve methodological issues. In this context, the research adopted a qualitative and quantitative approach. The methodology used was linked to the inductive and deductive method; at the same time, a correlational and experimental research level were determined. For this purpose, the population consisted of teachers and students from the following institutions: "Oswaldo Castro" Educational Unit, "Raymundo Aveiga" Educational Unit, and "Gonzalo Abad" Educational Unit in the city of Chone, Manabí province. The sample consisted of a total of 60 students; 20 students from each institution. In the data collected during the research, based on the use of strategies based on the neuropedagogy of the visual arts, the objective was to identify and capture, through drawings, the roles of the different characters in the aforementioned excerpt from the novel. At the same time, when calculating the average grades of the experimental group, the following scores were obtained: "Oswaldo Castro" Educational Unit 5.0, "Raymundo Aveiga" Educational Unit 5.3 and "Gonzalo Abad" Educational Unit 5.7, which showed that there was a significant difference between groups when evaluating the exercise.